Influence of the Correction of Cycloid Tooth Bevel Gear Cutter Head Radius on the Tooth Surface Contact Performance - Han Zhengyang; Deng Xiaozhong; Nie Shaowu; Geng Longlong (Jixie chuandong)
Aiming at the selection of parameter of the cycloid bevel gear cutter,the influence of radial correction of cutter on the tooth surface contact is studied. The mathematical model of cycloid bevel gears is established based on the cutter head and the formation principles of production gears. The contact analysis of different curvature tooth surface is carried out. Through example analysis,the impact of the correction of cutter radius on the relative principal curvature on meshing reference point is researched. The TCA program is written,and the teeth surface contact patterns of the different corrections of the tangential radius of the cutter head is got. Through the three-dimensional software,the three-dimensional model of big and small gear is established and the virtual assembly is carried out. The instantaneous contact oval is obtained by the determinate interference on the reference point. The rule that length of contact area is shorter with the increase of cutter radius correction is obtained by contrastive and quantitative analysis. The reference for the design and calculation of the parameter of the cycloid bevel gear cutter is provided.